Biskupia troska św. Augustyna o wychowanie i wykształcenie kapłanów - Eckmann, Augustyn (Verbum Vitae, 2012)
Future priests should want the good of the faithful and of the Church. In the “monasterium clericorum”, common prayer was deemed the superior religious practice. Also meals were eaten together and the seminarians went to bed at the same time. Applying to the Episcopal seminary, a candidate committed himself to voluntary poverty. The bishop taught clerical students to love loneliness and to become virtuous – especially to have the virtues of love,obedience, justice, prudence, and first of all, humility. Manual work and studying were also obligatory. The bishop formulated his recommendations on the reading of classical authors in three works: “De ordine”, “Epistola ad Dioscorum” and “De doctrina Christiana”. Reading classical authors prepares seminarians for the study of Holy Scriptures and works by Christian writers.